1982
DOI: 10.1104/pp.70.1.179
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic O2 Exchange Kinetics in Isolated Soybean Cells

Abstract: Light-dependent 02 exchange was measured in intact, isolated soybean (Glycine max. var. Williams) cells using isotopicaHly labeled 02 and a mass spectrometer. The dependence of 02 exchange on 02 and C02 was investigated at high light in coupled and uncoupled cells. With coupled cells at high 02, 02 evolution followed similar kinetics at high and low C02. Steady-state rates of 02 uptake were insignificant at high C02, but progressively increased with decreasing C02. At low C02, steady-state rates of 02 uptake w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
0

Year Published

1983
1983
1989
1989

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 18 publications
(45 reference statements)
4
37
0
Order By: Relevance
“…At low light, less OAA was required to suppress 02 uptake than at high light and a greater suppression was observed. This is also analogous to data obtained with isolated thylakoids where more NADP+ is required to suppress 02 uptake at high light than at low light (1 1 even under conditions where photorespiration is inhibited (5,10).…”
Section: Methodssupporting
confidence: 71%
See 3 more Smart Citations
“…At low light, less OAA was required to suppress 02 uptake than at high light and a greater suppression was observed. This is also analogous to data obtained with isolated thylakoids where more NADP+ is required to suppress 02 uptake at high light than at low light (1 1 even under conditions where photorespiration is inhibited (5,10).…”
Section: Methodssupporting
confidence: 71%
“…However, in the presence of 3-PGA, 02 uptake was saturated by quite low 02 concentrations (Fig. 2), similar to C3 cells and chloroplasts in the presence of saturating bicarbonate (5,10). In the presence of OAA, the 02 uptake was even less sensitive to 02 tension (Fig.…”
Section: Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…An energy overflow would probably increase in nondividing cells with gross photosynthesis identical (Table I) (8) concluded that in leaves, other components than RuBP oxygenase contributed to less than 5% of the CO2 inhibition of light oxygen uptake. Taking into account these previous data, we consider that the main source of difference, in our results, between RuBP oxygenase activity and photorespiration measured as described resulted from the differences of the CO2 level in the CO2-limiting conditions for the various samples (check Table II (16), gross photosynthesis, and oxygen uptake activities (3,4,7).…”
Section: Materials and Methods Culture Conditions And Materials Preparmentioning
confidence: 99%